Compliance with Updated Sepsis Bundles to Meet New Sepsis Core Measure in a Tertiary Care Hospital. Issue 3 (March 2017) - Ramsdell, Taylor H.; Smith, April N.; Kerkhove, Eric
Background: The updated Surviving Sepsis Campaign care bundles are associated with improved outcomes in patients with sepsis, yet adherence to the bundles remains inconsistent. The Centers for Medicare & Medicaid Services has adopted similar care bundles as a core measure that went into effect with October 1, 2015 discharges. Objective: The aim of this study was to assess bundle compliance, length of stay (LOS), and in-hospital mortality before and after introduction of the new sepsis core measure. Methods: A retrospective cohort study was conducted in 158 patients with a diagnosis of severe sepsis or septic shock from April 2015 to February 2016. The before group ( n = 48) consisted of sequential patients discharged from April 1, 2015 to September 30, 2015 (prior to core measure implementation), and the after group ( n = 110) consisted of sequential patients discharged from October 1, 2015 to February 29, 2016 (after core measure implementation). Results: Significant improvement was seen in the after group compared to the before group for bundle compliance with the 3-hour (66.4% vs 31.3%; p < 0.01) and 6-hour (75.5% vs 41.7%; p < 0.01) components and the overall core measure (51.8% vs 16.7%; p < 0.01). In-hospital mortality was lower in the after group compared to the before group (14.5% vs 27.1%; p = 0.05), but this difference was not statistically significant. There was no significant difference in LOS. Conclusions: The study found a significant increase in compliance with the sepsis care bundles since the implementation of this core measure. Increased adherence to the care bundles may improve in-hospital survival.